Zabawki dziecięce w niepublikowanych wspomnieniach rękopiśmiennych z terenu Królestwa Polskiego przełomu XIX i XX wieku (ze zbiorów Biblioteki Narodowej) - Nawrot-Borowska, Monika; Wałęga, Agnieszka (Biuletyn Historii Wychowania, 2026)
The results of the source analyses presented in this article complement the authors’ earlier research on previously unpublished manuscripts from the collections of the National Library, which explore various aspects of childhood and youth in the Kingdom of Poland at the turn of the nineteenth and twentieth centuries. The memoirs of both female and male diarists provide valuable insights into children’s toys and the games associated with them. These accounts offer an important contribution to the existing knowledge of toy history, particularly in identifying the repertoire of toys popular among children from different social backgrounds, including factory-made toys, more common among wealthier children, and handcrafted or improvised toys, which appeared across social groups. Attention is paid to the children’s gender and age, the materials from which the toys were made, the circumstances in which they were received, the places where they were acquired, and the ways in which they were used.